PERAN JALUR PEDESTRIAN MARGONDA DALAM MENDORONG INTERAKSI SOSIAL DAN AKTIVITAS EKONOMI LOKAL - Putu Jodhita Putri; Indah Aprilia; Tyas Wida Handoko (Media Bina Ilmiah, 2025)
Jalan Raya Margonda in Depok City acts as a rapidly growing economic centre, in line with its position as one of the protocol roads in Depok City. The existence of the pedestrian route is a crucial element that not only supports the continuity of businesses on the route, but also encourages more intense social interaction between consumers and businesses. This study aims to analyse the role of the pedestrian route on Jalan Margonda in encouraging social interaction and local economic activity. It also seeks to identify the impact of the pedestrian route on improving accessibility, consumer convenience, and the attractiveness of UMKMs operating in the Margonda area. The method used in this research is a descriptive method with qualitative data collection techniques involving in-depth interviews with pedestrian users, experts, and economic actors in the area. The results of the analysis show that the pedestrian on Jalan Margonda has not fully played a role in encouraging social interaction and local economic activity. This is due to the lack of proper spatial arrangements for UMKM actors, the lack of role of the Government and related agencies to disseminate information, as well as the lack of two-way communication between the government, the community, and other related parties, which has an impact on the lack of public awareness so that the drive to create social interaction and local economic activity on the pedestrian path has not been realised.